Chilean Version of the Empathy Quotient (Eq) Scale: Adaptation and Psychometric Properties - Fernandez-Tapia, A; Baeza-Ugarte, C (Cambridge University Press, 2021)
We evaluated the psychometric properties of the empathy quotient (EQ) scale translated to Spanish in Chile. We estimated its structural validity, and its construct validity with other convergent measures of empathy and attachment, as well an inversely associated construct such as aggression. We used a general sample of students and community individuals (n = 336). Participants completed the EQ, Interpersonal Reactivity Index (IRI), and Buss-Perry Aggression Questionnaire (BPAQ). Another exclusively community group (n = 102) completed Collins Adult Attachment scale and the EQ. CFA and ESEM analyses confirmed the structural model fit of the data to three previously reported dimensions of the EQ: cognitive empathy (CE), emotional reactivity (ER) and social skills (SS). Sex-differences in emotional reactivity, and the predicted relationships with the convergent measures were observed. The current Chilean version of the EQ resulted in an appropriate multidimensional measurement of empathy. Finally, providing a specific social skills dimension extends the traditional conception of cognitive and affective empathy to the social realm in the Chilean context. © Universidad Complutense de Madrid and Colegio Oficial de Psicólogos de Madrid 2021.